Chirality sensing of terpenes, steroids, amino acids, peptides and drugs with acyclic cucurbit[n]urils and molecular tweezers. Issue 34 (7th April 2020) - Prabodh, Amrutha; Bauer, Daniel; Kubik, Stefan; Rebmann, Philipp; Klärner, Frank Gerritt; Schrader, Thomas; Delarue Bizzini, Lorenzo; Mayor, Marcel; Biedermann, Frank
Abstract : Achiral chromophoric tweezer-shaped molecular hosts were found to respond with characteristic Circular Dichroism spectra to the presence of micromolar concentrations of chiral hydrocarbons, terpenes, steroids, amino acids and drugs in water. Abstract : Achiral chromophoric hosts, i.e. acyclic cucurbit[ n ]urils and molecular tweezers, were found to respond with characteristic Circular Dichroism (CD) spectra to the presence of micromolar concentrations of chiral hydrocarbons, terpenes, steroids, amino acids and their derivates, and drugs in water. In favourable cases, this allows for analyte identification or for reaction monitoring.